Evaluating the psychometric properties of the Hispanic Stress Inventory-2 Simplified version among a diverse sample of Latinos who smoke. - Ruthmarie Hernández-Torres; Francisco Cartujano-Barrera; Evelyn Arana-Chicas; Arlette Chávez-Iñiguez; Vignya Dontu; Shan Gao; Xueya Cai; Eida Castro-Figueroa; Deborah J Ossip; Ana Paula Cupertino (PLoS ONE, 2024)
Objective Acculturation stress can negatively impact Latinos immigrant mental and physical health related behaviors such as smoking. It is essential to have validated and updated instruments that allow the evaluation of acculturation stress on this population. This study aims to evaluate the psychometric properties of an abbreviated version of the Hispanic Stress Inventory Version 2 (HSI2) immigration scale among Latinos who smoke. Methods The study consisted of a secondary data analysis from a baseline assessment of Decídetexto, a mobile health (mHealth) smoking cessation randomized clinical trial. Of 457 Latinos included in the parent study, 352 immigrants who smoke were included. Construct validity was analyzed by completing a Pearson correlation coefficient matrix. Structural validity was analyzed using an Exploratory Factor Analysis (EFA). Cronbach alpha analysis was used to estimate the internal consistency of the items constituting a factor. Results The results included an abbreviated version of the HSI2 including 52 items. From the Pearson correlation coefficient matrix with a cutoff point of 0.4, 22 of the 52 items were excluded. From the Pearson correlation coefficient matrix with a cutoff point of 0.4, 22 items were excluded. Exploratory Factor Analysis (EFA) results in six factors extracted, explaining 69.1% of the variance. According to the EFA, two items were relocated in different factors from the original scale. The HSI2 30 items scale reflected excellent reliability with a Cronbach's alpha coefficient of 0.93. The six factors reflect acceptable to excellent reliability, ranging from 0.77-0.93 across factors. The median for the HSI2 total score was 34.00 (25-45) out of a possible total score of 150. Conclusion Results confirmed acceptable psychometric properties of the HSI2 simplified 30-item version and provided a reliable and shorter measure of acculturation stress for Latinos groups. Having a valid and reduced measure of acculturation stress is the first step in understanding diverse ethnic groups of Latinos that are at higher risk of presenting health risk behaviors such as smoking. The present results provided the possibility of assessing the impact of acculturation stress among adults who smoke.